Efficient Wireless Drone Charging Pad for Any Landing Position and Orientation - Tommaso Campi; Silvano Cruciani; Francesca Maradei; Mauro Feliziani (Energies, 2021)
A wireless charging pad for drones based on resonant magnetic technology to recharge the internal battery is presented. The goal of the study was to design a robust, reliable and efficient charging station where a drone can land to automatically recharge its battery. The components of the wireless power transfer (WPT) system on board the drone must be compact and light in order not to alter the payload of the drone. In this study, the non-planar receiving coil of the WPT system is integrated into the drone’s landing gear while the transmitting pad is designed to be efficient for any landing point and orientation of the drone in the charging pad area. To meet these requirements, power transmission is accomplished by an array of planar coils integrated into the ground base station. The configuration of the WPT coil system, including a three-dimensional receiving coil and a multicoil transmitter, is deeply analyzed to evaluate the performance of the WPT, considering potential lateral misalignment and rotation of the receiving coil due to imprecise drone landing. According to the proposed configuration, the battery of a light drone (2 kg in weight and 0.5 kg in payload) is recharged in less than an hour, with an efficiency always greater than 75%.